1993
DOI: 10.1165/ajrcmb/8.6.626
|View full text |Cite
|
Sign up to set email alerts
|

Aspartic Proteinases in Normal Lung and Interstitial Pulmonary Diseases

Abstract: Two aspartic proteinases, pepsinogen II (PgII) and cathepsin E (CathE), were identified immunocytochemically in lung epithelia. In normal lung, type II pneumocytes were characterized by PgII immunoreactivity of variable intensity, while bronchiolar Clara cells reacted with CathE antibodies. With the exception of small groups of nonciliated bronchial cells overlying lymphoid follicles, no other CathE-immunoreactive cell was found in the lung. Immunoblots of crude protein extracts of lung tissue using PgII and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…CTSE is an intracellular aspartic protease that can be found at the gastric surface (42), in neuronal cells, and is also expressed at the infiltration zone of gastric carcinomas (43), cervical adenocarcinomas (44), and pancreatic ductal carcinomas (45). CTSE is suspected to be involved in the execution of neuronal death pathways (46) and parenchymal remodeling that occurs in fibrosing lung disease (47). It also has a role in antigen processing by hydrolyzing antigenic peptides and the invariant chain (CD74) which influences the expression and peptide loading of MHC II molecules in professional and nonprofessional antigen-presenting cells Abbreviations: OS, overall survival; PFS, progression-free survival; RFS, recurrence-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…CTSE is an intracellular aspartic protease that can be found at the gastric surface (42), in neuronal cells, and is also expressed at the infiltration zone of gastric carcinomas (43), cervical adenocarcinomas (44), and pancreatic ductal carcinomas (45). CTSE is suspected to be involved in the execution of neuronal death pathways (46) and parenchymal remodeling that occurs in fibrosing lung disease (47). It also has a role in antigen processing by hydrolyzing antigenic peptides and the invariant chain (CD74) which influences the expression and peptide loading of MHC II molecules in professional and nonprofessional antigen-presenting cells Abbreviations: OS, overall survival; PFS, progression-free survival; RFS, recurrence-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…Cathepsin family members are involved in the remodelling of ECM proteins under inflammatory conditions. 45 Cathepsins L and E degrade collagen and elastin, and have a role in the pathogenesis of artheriosclerosis and lung emphysema/fibrosis. 45 Destruction of elastin-rich tissue is furthermore associated with local accumulation of macrophages containing high levels of cathepsins B and L. The aspartic proteinase cathepsin D also has the potential to initiate a proteolytic cascade, and to degrade and remodel ECM.…”
Section: How It Starts: Tissue Damage Caused By Intestinal Inflammationmentioning
confidence: 99%
“…In antigen presenting cells, such as macrophages and microglia, cathepsin E is mainly localized in the endosomal compartment (2,3). Previous studies have demonstrated that cathepsin E is important for exogenous antigen processing via the major histocompatibility complex class II presenting system (3)(4)(5) and is increasingly expressed in inflammatory cells within and nearby carcinomas (6), Clara cells, and the reactive type II pneumocytes (7,8). Recent gene or protein expression profiles have demonstrated the increased expression of cathepsin E in several types of carcinomas (9 -12), which is significantly associated with survival.…”
mentioning
confidence: 99%